Selection Processing in Noun and Verb Production in Left- and Right-Sided Parkinson's Disease Patients - Di Tella, Sonia; Baglio, Francesca; Cabinio, Monia; Nemni, Raffaello; Traficante, Daniela; Silveri, Maria C. (Frontiers in Psychology, 2018)
Verbs are more difficult to produce than nouns. Thus, if executive resources are reduced as in Parkinson’s disease (PD), verbs are penalised compared to nouns. However, in an experimental condition in which it is the noun that must be selected from a larger number of alternatives compared to the verb, it is the noun production that becomes slower and more prone to errors. Indeed, patients are slower and less accurate than normal subjects when required to distinguish nouns from verbs (VN) in a morphology derivation tasks (e.g., ‘osservazione’ from ‘osservare’) [‘observation’ from ‘observe’] than verbs from nouns in a morphology generation task, in which only a verb can be generated from the noun (NV) (e.g., ‘fallire’ from ‘fallimento’) [‘to fail’ from ‘failure’]. In the Italian language morphology, in fact, generation and derivation tasks differ in the number of lexical entries among which the response must be selected. The left Inferior Frontal Gyrus (IFG) has been demonstrated to be involved in selection processes. In the present study, we explored if the ability to select words is related to the cortical thickness of the left IFG. Twelve right-sided PD with nigrostriatal hypofunctionality in the left hemisphere (RPD-LH), 9 left-sided PD with nigrostriatal hypofunctionality in the right LPD-RH) and 19 healthy controls (HC) took part in the study. NV and VN production tasks were administered; accuracy and reaction times (RTs) were collected. All 40 subjects received a structural MRI examination. Cortical thickness of the IFG and volumetric measurements for subcortical regions, thought to support selection processes, were computed using FreeSurfer. In VN derivation tasks RPD-LH patients were less accurate than LPD-RH patients (accuracy: 66 % vs. 77 %). No difference emerged among the three groups in RTs. Task accuracy/RTs and IFG thickness showed a significant correlation only in RPD-LH. Not only nouns (as expected) but also verbs were correlated with cortical thickness. This suggests that the linguistic nature of the stimuli along with executive resources are both relevant during word selection processes. Our data confirm that executive resources and language interact in the left IFG in word production tasks.